2010
DOI: 10.1097/jsm.0b013e3181c96722
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Active Stretching Technique and Static Stretching Technique on Hamstring Flexibility

Abstract: Active stretching produced the greater gain in the AKER test, and the gain was almost completely maintained 4 weeks after the end of the training, which was not seen with the passive stretching group. Active stretching was more time efficient compared with the static stretching and needed a lower compliance to produce effects on flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 16 publications
2
33
0
2
Order By: Relevance
“…Because of the retrospective design of the current study, we can only speculate as to why HIS mechanical therapy significantly improved knee extension with both worker's compensation and non-compensation patients. It has been previously reported that shorter, more time efficient bouts of stretching may improve patient compliance and the efficacy of a treatment protocol[36], and we suspect that the reduced amount of daily use, as well as the overall shorter treatment durations associated with HIS mechanical therapy may have improved patient compliance, thus leading to more consistent range of motion improvements. Not only was motion improved with the use of adjunctive HIS mechanical therapy, the improvements were maintained at the most recent follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…Because of the retrospective design of the current study, we can only speculate as to why HIS mechanical therapy significantly improved knee extension with both worker's compensation and non-compensation patients. It has been previously reported that shorter, more time efficient bouts of stretching may improve patient compliance and the efficacy of a treatment protocol[36], and we suspect that the reduced amount of daily use, as well as the overall shorter treatment durations associated with HIS mechanical therapy may have improved patient compliance, thus leading to more consistent range of motion improvements. Not only was motion improved with the use of adjunctive HIS mechanical therapy, the improvements were maintained at the most recent follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…Son diversos los autores que destacan los beneficios de este trabajo de flexibilidad activa 16,17,27 . Esta forma de entrenamiento de la flexibilidad conlleva una unión del trabajo de fuerza y flexibilidad que contribuye a un equilibrio entre movilidad y estabilidad de columna, necesario para tener una espalda sana, indolora y funcional 28 , si se comparan con estudios de control postural mediante plataforma de fuerzas, como los de Fort Vanmeerhaeghe et al 29 .…”
Section: Discussionunclassified
“…To gain hamstring flexibility static and dynamic stretching exercises were generally used. Static stretching exercises are most commonly used to prevent from injuries, and generally improve flexibility in 3-6 weeks (19,20,28,29). Ayala et al showed that approximately 8 degrees of flexibility gain could be achieved in 4 weeks, 13 degrees of flexibility gain in 8 weeks and 15 degrees of flexibility gain in 12 weeks with static stretching 3 times in a week in subjects with tight hamstrings (29).…”
Section: Discussionmentioning
confidence: 99%